Novel Current-Conveyor-Based Single-Element-Controlled Oscillator Employing Grounded Resistors and Capacitors - Muhammad Taher Abuelma'atti; Abdallah Al-Ali Al-Ghumaiz (Active and Passive Electronic Components)
A novel single-element-controlled oscillator using two negative first-generation current-conveyors, two grounded capacitors and three grounded resistors is presented. The proposed circuit enjoys independent oscillation control through a single grounded resistor and independent frequency control through a single grounded resistor or a single grounded capacitor.